2016
DOI: 10.1523/eneuro.0240-16.2016
|View full text |Cite
|
Sign up to set email alerts
|

Integrative Analysis of Disease Signatures Shows Inflammation Disrupts Juvenile Experience-Dependent Cortical Plasticity

Abstract: Visual Abstract

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
29
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
5
1

Relationship

4
2

Authors

Journals

citations
Cited by 18 publications
(31 citation statements)
references
References 70 publications
(85 reference statements)
2
29
0
Order By: Relevance
“…We used Limma [28] to quantile normalized raw microrray probe-level data and RankProd [29] to compute rank-based differential expression of mouse genes, which we mapped to orthologous human genes using the Mouse Genome Informatics homology reference to yield 176 and 98 gene signatures (juvenile wild-type and adult Lynx1 −/− respectively), 35 of which were shared (Fisher Exact Test: OR=37.1, 95% CI = 23.8–58.0, p < 2.2 ×10 −16 , replication of comparison found in [14]) (Figure 1a). Both juvenile and Lynx1 −/− mice have elevated experience-dependent plasticity, whereas adult wild-type mice have reduced plasticity.…”
Section: Methodssupporting
confidence: 52%
See 4 more Smart Citations
“…We used Limma [28] to quantile normalized raw microrray probe-level data and RankProd [29] to compute rank-based differential expression of mouse genes, which we mapped to orthologous human genes using the Mouse Genome Informatics homology reference to yield 176 and 98 gene signatures (juvenile wild-type and adult Lynx1 −/− respectively), 35 of which were shared (Fisher Exact Test: OR=37.1, 95% CI = 23.8–58.0, p < 2.2 ×10 −16 , replication of comparison found in [14]) (Figure 1a). Both juvenile and Lynx1 −/− mice have elevated experience-dependent plasticity, whereas adult wild-type mice have reduced plasticity.…”
Section: Methodssupporting
confidence: 52%
“…Lynx1 −/− mice have elevated, juvenile-like plasticity [15] and were used to control for non-plasticity aspects of the juvenile signature. We defined putative plasticity genes as the 35 shared between the two signatures (Fisher Exact Test: OR=37.1, 95% CI = 23.8–58.0, p < 2.2 ×10 −16 , this statistic reproduced as in [14]). Interestingly, using gene set enrichment we found that these genes are predominantly enriched for immune processes, including gene sets related to neutrophil degranulation, defense response to fungus, immune cell chemotaxis, apoptotic pathways, and cytokine production (Table 2).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations